Functional Analysis of Hydrolethalus Syndrome Protein HYLS1 in Ciliogenesis and Spermatogenesis in Drosophila - Hou, Yanan; Wu, Zhimao; Zhang, Yingying; Chen, Huicheng; Hu, Jinghua; Guo, Yi; Peng, Ying; Wei, Qing (Frontiers in Cell and Developmental Biology, 2020)
Cilia and flagella are conserved subcellular organelles, which arise from centrioles and play critical roles in development and reproduction of eukaryotes. Dysfunction of cilia leads to life-threatening ciliopathies. HYLS1 is an evolutionarily conserved centriole protein, which is critical for ciliogenesis, and its mutation causes ciliopathy-hydrolethalus syndrome. However, the molecular function of HYLS1 remains elusive. Here, we investigated the function of HYLS1 in cilia formation using the Drosophila model. We demonstrated that Drosophila HYLS1 is a conserved centriole and basal body protein. Deletion of HYLS1 led to defects in sensory cilia and in spermatogenesis. Importantly, we found that Drosophila HYLS1 is essential for giant centriole/basal body elongation in spermatocytes, and is required for spermatocyte centriole to efficiently recruit pericentriolar material (PCM) and for spermatids to assemble the proximal centriole-like structure (PCL, the precursor of the second centriole for zygote division). Hence, by taking advantage of the giant centriole/basal body of Drosophila spermatocyte, we uncover previously uncharacterized roles of HYLS1 in centriole elongation and assembly.